Close up of brown skua head - Young, Euan (School of Biological Sciences, University of Auckland, 1992)
The characteristic hooked bill of the skuas is due to a prominent distal 'nail' on the upper mandible. This feature is absent in gulls and is indicative of the skuas' predatory lifestyle.